Aging effect of cross-modal interactions during audiovisual detection and discrimination by behavior and ERPs - Ren, Yanna; Li, Yan; Xu, Zhihan; Luo, Rui; Qian, Runqi; Duan, Jieping; Yang, Jiajia; Yang, Weiping (Frontiers in Aging Neuroscience, 2023)
Numerous studies have shown that aging greatly affects audiovisual integration; however, it is still unclear when the aging effect occurs, and its neural mechanism has yet to be fully elucidated. Hence, we assessed the AVI of older (n=40) and younger (n=45) adults using simple meaningless stimulus detection and discrimination tasks. The results showed that the response was significantly faster and more accurate for younger adults than for older adults in both the detection and discrimination tasks. The AVI was comparable for older and younger adults during stimulus detection (9.37% vs. 9.43%); however, the AVI was lower for older than for younger adults during stimulus discrimination (9.48% vs. 13.08%) behaviorally. The EEG analysis showed that comparable AVI amplitude was found at 220–240 ms for both groups during stimulus detection and discrimination, but there was no significant difference between brain regions for older adults but a higher AVI amplitude in the right posterior for younger adults. Additionally, a significant AVI was found for younger adults in 290–310 ms but was absent for older adults during stimulus discrimination. Furthermore, significant AVI was found in the left anterior and right anterior at 290–310 ms for older adults but in the central, right posterior and left posterior for younger adults. These results suggested that the aging effect of AVI occurred in multiple stages, but the attenuated AVI mainly occurred in the later discriminating stage attributed to attention deficit.